Saturday

April 19, 2014

April 19, 2014

Posted by **marie** on Sunday, December 20, 2009 at 8:35pm.

- math -
**drwls**, Monday, December 21, 2009 at 6:45amFirst, expand the term in parentheses (do the multiplication by 6)

6 -18x +6 = -42

Then, more all the constants to the right (changing signs when you do).

-18x = -42 -6 -6 = -54

Multiply both sides by -1

18x = 54

Divide both sides by 18.

x = 54/18 = 3

**Related Questions**

Math(Please check answers) - Factor completely. If the polynomial cannot be ...

math - 3x-5/6=7x+4/4 If you mean (3x-5)/6= (7x+4)/4 , then 12 x - 20 = 42 x + 24...

Algebra - (3x+4)/(3x-4)+(3x-4)/(3x+4) --------------------------- Divide top by ...

math help - 6-6(3x - 1)= -42

math - Which comparison sentence best represents the equation? 6x7=42 7 is 6 ...

Math- Corrections - (-9)-4w+7w=42 I thought I knew how to do this, but my ...

math - write as an addition problem (-21)-42 A) (-21)-(-42) B) (-21)+42 c) (-21...

math - I forgot how to add and subtract mixed # fractions. How do you do it? ex...

Math (Calculus AB) - An equation to the graph of y=x^3+3x^2+2 at its point of ...

Math - If g(x)= 3x-8, find g[g(-4)]. A)-68 B)4 C)-20 D)52 I got C 3x-8[3x-8(-4...